2010
DOI: 10.1521/suli.2010.40.4.319
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Films: The Impact of Suicide Portrayals on Nonsuicidal Viewers' Well-Being and the Effectiveness of Censorship

Abstract: The effects of suicide films on recipients' emotional and mental state, as well as the influence of censorship, was studied. Nonsuicidal subjects watched the original or a censored version of a suicide film or a drama without suicide. Data were collected by questionnaires. The viewing led to a deterioration of mood and an increase in inner tension and depression scores, but also to a rise in self-esteem and life satisfaction and to a drop in suicidality. There were no relevant differences between the film grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
1
23
1
3
Order By: Relevance
“…However, a more recent experimental survey study conducted on non-suicidal adolescents found that while suicide fi lms did lead to a deterioration of mood, no increase in suicidality was reported (32) . This is one of the very few recent suicide studies on adolescents that was a true experimental study, in that half of the participants were assigned to watch a movie with suicidal content, while the other half viewed a similar movie with no suicidal content.…”
Section: Adolescent Suicide In New York Citymentioning
confidence: 96%
See 1 more Smart Citation
“…However, a more recent experimental survey study conducted on non-suicidal adolescents found that while suicide fi lms did lead to a deterioration of mood, no increase in suicidality was reported (32) . This is one of the very few recent suicide studies on adolescents that was a true experimental study, in that half of the participants were assigned to watch a movie with suicidal content, while the other half viewed a similar movie with no suicidal content.…”
Section: Adolescent Suicide In New York Citymentioning
confidence: 96%
“…This is one of the very few recent suicide studies on adolescents that was a true experimental study, in that half of the participants were assigned to watch a movie with suicidal content, while the other half viewed a similar movie with no suicidal content. It is possible that Till and colleagues (32) were forced to accept the null hypothesis because their study was conducted (i) cross-sectionally and (ii) on community adolescents without pre-established suicide risk. These fi ndings would be interesting to explore both within NYC and beyond, regarding whether similar results would be found among previously suicidal adolescents and/or longitudinally.…”
Section: Adolescent Suicide In New York Citymentioning
confidence: 99%
“…This phenomenon is often referred to as copycat behavior or Werther effect (see Niederkrotenthaler et al, 2009Niederkrotenthaler et al, , 2010Pirkis & Blood, 2001a). Some studies found an increase of depression among nonsuicidal viewers of a suicide film (e.g., Till, Niederkrotenthaler, Herberth, Vitouch, & Sonneck, 2010;Till et al, 2011) or identified associations between exposure to suicide on television and suicidality (e.g., Martin, 1996). Vice versa, particularly individuals in adverse life circumstances, who already think about suicide, are most likely to seek media contents on suicide and to act out their suicidal feelings when exposed to suicide-related media accounts (Etzersdorfer, 2008;Etzersdorfer & Sonneck, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Based on Festinger's social comparison theory, media consumers are known to compare themselves with protagonists shown in media products (Festinger, 1954;Till et al, 2010), and with regard to Martin who was suicidal but managed to cope with his crisis, study participants who did not identify with Martin may have shown some "contrast effect", i.e. they may have arrived at the conclusion that their own lives were different and better than that of the protagonist, resulting in a decrease of their suicidal cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research conceptualized potential identification either indirectly as a content related factor (e.g., by focusing on similarities between the featured protagonist and the audience in terms of age and sex; e.g. Fu & Yip, 2009;Niederkrotenthaler et al, 2009), or directly as individual factor, by measuring 5 Stories of recovery / identification / exposure intention identification in the audience (Till et al, in press;Till, Niederkrotenthaler, Herberth, Vitouch, & Sonneck, 2010;. It is still unclear which characteristics of a role model determine if or to what extent an audience identifies with the model (Cohen, 2001).…”
Section: Stories Of Recovery / Identification / Exposure Intentionmentioning
confidence: 99%